The Relationship of Age, Surgery Type, and Time to Surgery with Post-Operative Outcome of Open Tibial Fracture Grade III at RSUP Sanglah Denpasar in 2018-2020 - Kesumaputri, Komang Diah Kurnia; Subawa, I Wayan; Dewi, Kadek Ayu Candra; Meregawa, Putu Feryawan (E-Jurnal Medika Udayana, 2023)
Open tibial fracture is one of the most common lower extremity fractures in the world, especially in Denpasar City. Clinically, open tibial fracture grade III has higher risk of worse outcome, such as infection and bone healing complication than grades I and II, thus it should be evaluated further regarding risk factors affecting that occurrence. This research aims to know the relationship between several risk factors, those are age, surgery type, and time to surgery with postoperative outcomes in open tibial fractures grade III in terms of clinical, radiological, and functional based on Johner-Wruhs criteria. This research used cross-sectional method and used patients with open tibial fracture grade III who underwent surgery at RSUP Sanglah Denpasar in 2018-2020. Based on the data collection, there were 31 patients fulfilled the inclusion and exclusion criteria. The data collected were characteristics and postoperative outcome assessed using Johner-Wruhs criteria which consisted of 4 categories. From Kendall Tau correlation test, there was no significant relationship between age and outcome (p=0,215) and a significant relationship between time to surgery and outcome (p=0,021). Moreover, the results of Fisher’s Exact Test did not find significant relationship between surgery type and outcome (p=0,720). Based on the results, it can be concluded that time to surgery (debridement) has significant effect on postoperative outcome compared to age and surgery type. Time to debridement also has unidirectional relationship with outcome, which means the longer time to debridement, the worse outcome experienced by the patient. Keywords : open tibial fracture, surgery type, outcome, age, time to surgery